Health Beliefs and Perceptions of Trachoma in Communities on the Bijagos Archipelago of Guinea Bissau. (June 2015) - Thompson, Katie; Hutchins, Harry; Baio, Aramata; Cassama, Eunice; Nabicassa, Meno; Bailey, Robin; Last, Anna R.
ABSTRACT Purpose: The World Health Organization aims to eliminate blinding trachoma by 2020 using the SAFE strategy: Surgery for trichiasis, Antibiotics, Facial cleanliness and Environmental improvement. Trachoma is hyperendemic on the remote Bijagos Archipelago of Guinea-Bissau, West Africa. Sociocultural factors remain unexplored here, despite their potential impact on disease control, particularly through the "F" and "E" aspects. By examining these, we aim to illuminate this population's unreported health beliefs, hygiene behaviors and disease perceptions. This understanding will help to optimize future public health interventions, and guide the distribution of limited healthcare resources. Methods: Two unmatched interview series were conducted 1 year apart on Bubaque Island in the Bijagos Archipelago; one in rural villages using purposive snowball sampling, the other in a semi-urban settlement, using random-cluster sampling. Interviews were conducted and recorded in Kriolu, the local dialect, by a supervised local field assistant before translation into English for conventional content analysis. Results: Trachoma was unheard of in either series, despite ongoing local trachoma research. A heterogeneous range of disease etiology and preventative measures were suggested, but the importance of hygiene was more widely reported by semi-urban interviewees. Although western medicine was well regarded, traditional practices continued, particularly in the rural populations. Conclusions: Differences in knowledge, beliefs and behaviors were apparent between the two series. Despite widespread rudimentary knowledge of disease prevention, targeted education might benefit both communities, particularly basic hygiene education for rural communities. Healthcare access should also be improved for rural populations. The impact of these measures could be assessed by future fieldwork.